Striving for excellence: assessing the impact of university strategies on enhancing student services in Albanian public higher education - Leskaj, Etleva; Leskaj, Alfred; Lipi, Rudina (Frontiers in Education, 2024)
This paper examines the role of university strategies in enhancing student services, to create a conducive and supportive learning environment. Recognizing that the quality of student services is integral to students’ academic success, well-being, and overall experience, universities worldwide are increasingly prioritizing strategic initiatives to improve service delivery. This research synthesizes existing literature and empirical evidence to analyze the diverse strategies used by universities to improve student services and their impact on student satisfaction, retention, and success. In this article, the authors relied on secondary research in the literature of the field, as well as primary research, to fulfill the aim of this study, which is to assess student satisfaction with the services offered by higher education institutions based on their perspective, as an essential indicator for the implementation of the University’s strategy and the achievement of the objectives of this strategy. This study is based on Parasuraman’s Servqual model. The dependent variable in this study is the overall satisfaction of students at the University of Tirana. The independent variables are tangibleness, assurance, response, reliability, and empathy. The objectives are to: identify the dimensions of service quality; examine the relationship between the dimensions of service quality and student satisfaction; and assess the impact of each of the five dimensions of service quality individually on student satisfaction. The paper highlights empathy and reliability as important dimensions influencing student satisfaction. Recognizing this, the university should prioritize personalized attention to students, demonstrating a readiness to address their concerns and establish efficient channels for problem-solving. Based on the findings, the authors have made several recommendations, emphasizing the importance of student-centered approaches, institutional commitment, and strategic alignment in providing a supportive and enriching educational experience that supports student success and well-being.